2015
DOI: 10.1038/nn.3966
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 reductions exacerbate Alzheimer's disease vasculo-neuronal dysfunction and degeneration

Abstract: The glucose transporter GLUT1 at the blood-brain barrier (BBB) mediates glucose transport into the brain. Alzheimer's disease is characterized by early reductions in glucose transport associated with diminished GLUT1 expression at the BBB. Whether GLUT1 reduction influences disease pathogenesis remains, however, elusive. Here, we show that GLUT1 deficiency in mice overexpressing amyloid β-petpide (Aβ) precursor protein leads to: 1) early cerebral microvascular degeneration, blood flow reductions and dysregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
497
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(550 citation statements)
references
References 61 publications
26
497
2
Order By: Relevance
“…Recent work suggests that contribution of astrocytic glucose transporters is less significant than the importance of the vascular endothelial transporters (107). Further work also suggests that glial glucose transporters might not provide an appropriate target for preventing AD: as in drosophila AD models overexpression of GLUT1 in glia had no effect against Aβ induced neurotoxicity (108).…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%
“…Recent work suggests that contribution of astrocytic glucose transporters is less significant than the importance of the vascular endothelial transporters (107). Further work also suggests that glial glucose transporters might not provide an appropriate target for preventing AD: as in drosophila AD models overexpression of GLUT1 in glia had no effect against Aβ induced neurotoxicity (108).…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%
“…It has been reported that various peripheral pathologies that affect glucose levels lead to alterations in brain functions, including functions related to neuronal plasticity, memory, and learning (22,49). In Drosophila, it has been described that increase of the glucose transport induces a decrease in the neuronal damage induced by amyloid ␤ (50).…”
Section: Wnt Signaling Stimulates Glucose Utilization In Neuronsmentioning
confidence: 99%
“…In brain tissue, glucose is oxidized through glycolysis and oxidative phosphorylation to produce ATP, most of which is consumed by neurons during the recovery of ion gradients after synaptic transmission (19,20). In several models of neurological disorders, it has been shown that dysfunctional glucose utilization is a critical step in the onset and progression of disease (21,22). Accordingly, enhancing glucose utilization in vivo induces significant improvements in cognitive functions, such as memory and learning (23)(24)(25).…”
mentioning
confidence: 99%
“…These are designed to lower plasma glucose by promoting glycosuria, but there are encouraging signs that they may also have renoprotective effects, perhaps by lowering the elevated glucose concentrations in the proximal tubular cell, as well as having other relevant actions, including blood pressure reduction and weight loss. Tissue selectivity would be a prerequisite for any attempt to modulate tissue glucose uptake in humans because reduced blood-brain barrier glucose flux via GLUT1 is implicated in the development of neurodegenerative conditions such as Alzheimer's disease [18].…”
Section: What Might the Future Hold?mentioning
confidence: 99%